A [2.2]isoindolinophanyl-based carbene (iPC) ligand: synthesis, electronic and photophysical properties, and application in photocatalysis - Maity, Sabyasachi; Muthig, André Martin Thomas; Sen, Indranil; Mrózek, Ondřej; Belyaev, Andrey; Hupp, Benjamin; Steffen, Andreas (Technische Universität Dortmund, 2024)
Cyclic amino(alkyl) and cyclic amino(aryl) carbenes (cAACs/cAArCs) have been established as very useful ligands for catalytic and photonic applications of transition metal complexes. Herein, we describe the synthesis of a structurally related sterically demanding, electrophilic [2.2]isoindolinophanyl-based carbene (iPC) that bears a [2.2]paracyclophane moiety. The latter leads to more delocalized frontier orbitals and intense green fluorescence of (HiPC)OTf (2) from an intra-ligand charge transfer (1ILCT) state in the solid state. Base-promoted synthesis of the free carbene led to an unusual ring expansion and subsequent dimerization reaction, but the beneficial ligand properties can be exploited by trapping in situ at a metal center. The iPC ligand is a very potent π-chromophore, which participates in low energy metal-to-ligand (ML)CT transitions in [RhCl(CO)2(iPC)] (4) and IL-“through-space”-CT transitions in [Au(iPC)2]OTf (5). The steric demand of the iPC leads to high stability of 5 against air, moisture, or solvent attack, and ultralong-lived green phosphorescence with a lifetime of 185 μs is observed in solution. The beneficial photophysical and electronic properties of the iPC ligand, including a large accessible π surface area, were exploited by employing highly efficient energy transfer (EnT) photocatalysis in a [2+2] styrene cycloaddition reaction using 5, which outperformed other established photocatalysts in comparison.
Angewandte Chemie: International edition; 63(41)
Keywords: Carbene; Paracyclophane; Luminescence; Coordination chemistry; Photocatalysis; 540